A Chinese approach to protected areas: A case study comparison with the United States. (June 2017) - Miller-Rushing, Abraham J.; Primack, Richard B.; Ma, Keping; Zhou, Zhi-Qiang
Abstract: China is being transformed by economic development, urban migration, and social change. Environmental reporting on China has tended to focus on environment damage, especially air pollution. Relatively unnoticed in the West, however, China has invested in improving and expanding its system of protected areas. These protected areas follow varied models—they include nature reserves, forest parks, wetland parks, and more—and face challenges roughly similar to those of protected areas in the United States and many other countries. Unsurprisingly, though, there are important differences that make China's protected area program uniquely Chinese. Chinese protected areas have been largely created and continue to be developed with strong top-down authority, although national-level control is softening and other models are being tested. Several nature reserves have received influxes of government funding in recent years to improve and expand their infrastructure and activities to support conservation, tourism, and other uses. Chinese nature reserves also tend to have explicit zoning and economic activities designed to promote economic development in and around them; this emphasis on economic development is greater and takes a different approach in Chinese parks than is typical in Western park systems. Here we compare aspects of the Chinese and US investments in national parks and national nature reserves; we use two examples—Wudalianchi National Nature Reserve in China and Acadia National Park in the United States—to highlight similarities and differences. We conclude that each country's approach to protected areas has strengths and weaknesses in terms of conservation value, engagement with local communities, and sustainability, but that overall each country's protected areas program has structural deficiencies, particularly related to the allocation of funding, that undermine their ability to achieve their stated mission over the long term. The shortcomings in each country are different and may not be as substantial as the shortcomings of` national parks in many other countries, but they are critical nonetheless. Highlights: China is investing substantially in protected areas, especially highly visited sites. Emphasis on economic development can conflict with conservation goals. China has much less private involvement in protected areas than does the US. Inadequate funding limits the success of protected areas in China, US, and elsewhere.